Antipsychotic medication exposure, clozapine, and pneumonia: results from a self‐controlled study. (8th January 2020) - Rohde, C.; Siskind, D.; de Leon, J.; Nielsen, J.
Abstract : Objective: By using a self‐controlled design, we investigated whether antipsychotic medication exposure was associated with increased pneumonia risk and whether patients receiving clozapine were more likely to develop pneumonia than patients receiving other antipsychotic medications. Methods: Through nationwide health registers, we identified all out‐patients with schizophrenia initiating antipsychotic treatment. First, we estimated whether antipsychotic‐naïve patients with schizophrenia increased their risk of pneumonia after initiation of either a first‐ or second‐generation antipsychotic medication using a one‐year mirror‐image model. Afterward, similar analyses were made for individual second‐generation antipsychotics. Lastly, the rate of pneumonia for patients initiated on clozapine was compared to patients commenced on other second‐generation antipsychotics. Results: In total, 8355 antipsychotic‐naïve patients with schizophrenia were initiated on a first‐generation antipsychotic medication; 0.95% of the patients had developed pneumonia before exposure, compared to 0.68% after exposure ( P  = 0.057). Similar findings were made for the 8001 antipsychotic‐naïve patients with schizophrenia initiated on second‐generation antipsychotic medications, with 0.56% developing pneumonia before exposure compared to 0.55% after exposure ( P  = 1.00). Second‐generation antipsychotic medications did not increase the pneumonia risk, except for risperidone (increased by 0.32%; P  = 0.007) and clozapine, which gave the largest absolute increase in pneumonia risk although not significant (increased by 0.64%; P  = 0.10). The rate of pneumonia was higher after initiation of clozapine than for other second‐generation antipsychotic medications. Conclusion: Most antipsychotic medications were not found to increase the risk of pneumonia. Clozapine exposure might be associated with increased risk of developing pneumonia.